2016
DOI: 10.1103/physreve.93.052141
|View full text |Cite
|
Sign up to set email alerts
|

Spectral mapping of heat transfer mechanisms at liquid-solid interfaces

Abstract: Thermal transport through liquid-solid interfaces plays an important role in many chemical and biological processes, and better understanding of liquid-solid energy transfer is expected to enable improving the efficiency of thermally driven applications. We determine the spectral distribution of thermal current at liquid-solid interfaces from nonequilibrium molecular dynamics, delivering a detailed picture of the contributions of different vibrational modes to liquid-solid energy transfer. Our results show tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 45 publications
9
100
1
Order By: Relevance
“…We estimate the spectral phonon transmission coefficient of pristine MoS2 and the defected MoS2 with different defect concentration following the Ref. 41,42 . As shown in Based on our simulations, the phonon-defect scatterings should be responsible for the decrease of phonon transmission coefficient and the reduction of the thermal conductivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We estimate the spectral phonon transmission coefficient of pristine MoS2 and the defected MoS2 with different defect concentration following the Ref. 41,42 . As shown in Based on our simulations, the phonon-defect scatterings should be responsible for the decrease of phonon transmission coefficient and the reduction of the thermal conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…q(  is the frequency dependent heat flux across the imaginary cross-section (red dashed line in Fig. 3(a)), which can be calculated as 41,42  (7) where s t is the simulation time, "L" and "R" respectively denotes the left and right segment, which located at different sides of the imaginary cross-section. αβ F is the total force exerted by R segment.…”
Section: Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Kapitza conductance is extremely dependent on the structural details of the interface at the nanoscale since the characteristic dimensions are comparable to or less than the vibrational mean‐free paths. Nanostructuring at the interface has been efficiently used to tune the energy transport pathways across interfacial regions either by introducing roughness, nonplanar features, interface mixing, or by functionalizing the interface to alter the stiffness of the bonds …”
Section: Effect Of Nanostructuring and Surface Functionalizationmentioning
confidence: 99%
“…Nanostructuring at the interface has been efficiently used to tune the energy transport pathways across interfacial regions either by introducing roughness, [78,90,137,138] nonplanar features, [139][140][141] interface mixing, [137,142] or by functionalizing the interface to alter the stiffness of the bonds. [143][144][145][146][147][148][149][150][151] Experimental works have demonstrated that nonplanar features of nanofabricated fin-like projections with characteristic length scales of ≈100 nm can substantially increase the interfacial heat flow through an increase in the overall contact area. [139,140] Similarly, MD studies have also shown that these types of features (even down to sub-nanometer length scales) can be used to achieve an increase in h K .…”
Section: Effect Of Nanostructuring and Surface Functionalizationmentioning
confidence: 99%
“…MD simulation naturally includes all the orders of lattice anharmonicity. All these works [29][30][31][32][33][34][35][36][37][38] using equilibrium MD and nonequilibrium MD are based on the energy exchange rate formalism between materials A and B. A more general formula to include the three and many-body interactions is 29,[36][37][38]…”
Section: Introductionmentioning
confidence: 99%